Contemporary American foreign policy towards Syria (Al-Mostansiriyah journal for Arab and international studies, 2026)
Abstract : Syria, with its strategic qualifications and prominent regional position, received the attention of American foreign policy from before and after the end of World War II and the Cold War between the two poles, the United States of America and the former Soviet Union, and after it until the present day, when Syria and the entire region turned into an arena for competition between them over the expansion of influence. The United States of America tried to include Syria in its sphere of influence and prevent the expansion of Soviet-Russian influence. To achieve its goal, it resorted to various means. But Syria saw the American foreign policy biased towards Israel as a threat to it, so it strengthened its rapprochement with the Soviet Union and the Russians who supported it. For this reason, it came The study includes the decision-making process in American foreign policy towards Syria in the period between 1989-2004 through the following: - First: The objectives of contemporary American foreign policy towards Syria. Second: The means of implementing contemporary American foreign policy towards Syria.Keywords: American foreign policy, contemporary American history, American-Syrian relations.